2015
DOI: 10.1021/acs.jpca.5b05658
|View full text |Cite
|
Sign up to set email alerts
|

Ferric–Thiolate Bond Dissociation Studied with Electronic Structure Calculations

Abstract: The stability and reactivity of iron-sulfur clusters are fundamental properties for the biological function of these prosthetic groups. Here, we investigate the ferric-thiolate bond dissociation of model iron-sulfur tetrahedral complexes with high-level ab initio multiconfigurational electronic structure calculations. We find that the reaction mechanism is homolytic with a spin-crossing from the sextet state in the reactant to quartet state in the product. We also compare several density functionals and semiem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…The MAE observed for all functionals tested correspond to the TS of reactions C and E where left-right (multi-configurational) correlation is significant. 27 The performance of B3LYP-D3 and M06L is also good. Comparison with B3LYP shows that addition of dispersion corrections is important and justifies the good performance of M06 and M06L which account for dispersion in the original parametrizations.…”
Section: Performance Of Approximate Electronic Structure Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…The MAE observed for all functionals tested correspond to the TS of reactions C and E where left-right (multi-configurational) correlation is significant. 27 The performance of B3LYP-D3 and M06L is also good. Comparison with B3LYP shows that addition of dispersion corrections is important and justifies the good performance of M06 and M06L which account for dispersion in the original parametrizations.…”
Section: Performance Of Approximate Electronic Structure Methodsmentioning
confidence: 94%
“…Several molecular electronic structure methods were compared with the the CCSD(T) goldstandard level of theory in order to find suitable descriptions of FeS reactivity, following our previous studies. 12,13,16,17,27 Solvation and free energy contributions were evaluated with an all-atom hybrid QM/MM potential giving an accomplished view of water substitution reactions on iron and allowing the calibration of more approximate implicit solvent models. We found that geometries determined by the OLYP functional with a split-valence basis set and energetics obtained with a hybrid functional such as M06 or ωB97X-D3 and a triple-zeta basis set, both together with implicit solvation, provide a reasonably reliable and efficient procedure to model FeS reactivity in solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the prepared SPs were introduced to the effluent, erdite was rich in SPs and spontaneously hydrolyzed and generated various Fe/S-bearing complexes and clusters, such as =Fe(SH) 2 , =Fe(OH)(SH) and =Fe(SH) + [47]. These products, which are metastable, were further converted to Fe/S-bearing oxyhydroxide (such as =Fe-SH and =Fe-OH) through the homolytic cleavage of Fe-S-Fe bonds [48] after the release of OH − and HS − to the effluent (Figure 14). This phenomenon corresponds to the increase in the treated effluent pH from 7.3 to 8.6.…”
Section: Sp1 and Sp2 Characterisation After Electroplating Wastewatermentioning
confidence: 99%
“…A semiempirical potential specifically parametrized to model Fe-S bond dissociation 27 based on the PM6 general parametrization 45 with d-orbitals was also tested. Complete active space configuration interaction calculations 46 with 7 electrons in 7 orbitals were performed with orbitals determined from restricted-open shell (ROHF) calculations with fractional occupation.…”
Section: Quantum Chemical Calculationsmentioning
confidence: 99%